2007
DOI: 10.1056/nejmoa071422
|View full text |Cite
|
Sign up to set email alerts
|

Patent Foramen Ovale and Cryptogenic Stroke in Older Patients

Abstract: There is an association between the presence of patent foramen ovale and cryptogenic stroke in both older patients and younger patients. These data suggest that paradoxical embolism is a cause of stroke in both age groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
313
4
11

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 543 publications
(333 citation statements)
references
References 31 publications
5
313
4
11
Order By: Relevance
“…Depending on the classification system, cryptogenic strokes account for almost 30% of cases and are more common in young patients. Multiple studies have demonstrated an association between PFO and cryptogenic stroke [8,9] . Since the inner ear requires a high-energy metabolism and the IAA is an end artery with little collaterals from the otic capsule, the inner ear is particularly vulnerable to ischemia [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the classification system, cryptogenic strokes account for almost 30% of cases and are more common in young patients. Multiple studies have demonstrated an association between PFO and cryptogenic stroke [8,9] . Since the inner ear requires a high-energy metabolism and the IAA is an end artery with little collaterals from the otic capsule, the inner ear is particularly vulnerable to ischemia [10] .…”
Section: Discussionmentioning
confidence: 99%
“…PBE is considered a likely cause of stroke in young patients when more common causes are excluded. However, it can be important also in older patients [10] and as an independent factor even when other cerebrovascular risk factors are present [11].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of patent foramen ovale was significantly higher in the patients with stroke (40 percent) than in the control group (10 percent).Thy concluded that These results suggest that because of the high prevalence of clinically latent venous thrombosis, paradoxical embolism through a patent foramen ovale may be responsible for stroke more often than is usually suspected. Similarly Handke et al (23) stated that there's a strong significant association between cryptogenic stroke and PFO in younger patients .This can be explained by the fact that younger patients are less likely to have conventional ischemic stroke risk factors (hypertension, high cholesterol, diabetes mellitus, smoking) and so the probability that a PFO is the cause of stroke increases. Several postulated mechanisms were described by Berthet et al (24) ; The most famous is "paradoxical embolism", which is the passage of a thrombus from the peripheral venous system to the left cardiac cavities through the PFO which seems to be the most likely mechanism in patients with cryptogenic stroke associated to PFO, other potential mechanisms should also be considered.…”
Section: **Motor Deficitmentioning
confidence: 99%